Generalized Continua as Models for Materials with Multi-scale Effects or Under Multi-field Actions - Altenbach, Holm; Forest, Samuel; Krivtsov, Anton (Advanced Structured Materials,, 2013)
This volume presents contributions describing the micro- and macro-behaviours, new existence and uniqueness theorems, the formulation of multi-scale problems, etc. and now it is time to ponder again the state of matter and to discuss new trends and applications. The main focus is directed on the following items - Modelling and simulation of materials with significant microstructure, - Generalized continua as a result of multi-scale models, - Multi-field actions on materials resulting in generalized material models, and - Comparison with discrete modelling approaches.